Evidences of talc-white mica assemblage in low-grade metamorphic rocks from the internal zone of the Rif Cordillera (N Morocco) - Rodríguez-Ruiz, María Dolores; Abad, Isabel; Bentabol-Manzanares, María José; Ruiz-Cruz, María Dolores (Elsevier, 2020)
Talc-phengite intergrowths were identified in epizone rocks from the Beni Mezala unit (Internal Zone of the Rif). These rocks show the non-common assemblage quartz-K-feldspar-albite-phengite-talc-vermiculite-chlorite/vermiculite mixed-layers. Although X-ray diffraction patterns indicate the presence of talc, talc could not be observed petrographically. In contrast, transmission electron microscopy indicates that white mica consists of nanometer-sized intergrowths of phengite and talc. At the scanning electron microscope scale, these micas show anomalously high contents of Fe + Mg composition (with an average value of 0.51 atoms per formula unit, apfu). The subtraction of the talc component from the mica formula allowed to obtain a mica with a limited phengitic substitution K0.91Na0.03(Al1.74 Fe2+0.23Mg0.03Ti0.03)Σ=2.03(Si3.18Al0.82) which permits an estimation of minimum pressure (P) <4 kbar. This is coherent with the medium-P facies series determinate by the b-cell parameter of white micas (9.036 Å). The detailed study at nanometer scale shows a domain structure of talc within the white mica packets probably originated by exsolution from a metastable precursor mica with high Fe + Mg contents. This has been interpreted as a relic of a HP assemblage in a low-grade metamorphic context. The study at nanometer scale should be considered as they may have petrological implications.
https://openpolicyfinder.jisc.ac.uk/id/publication/11130
CGL2009-08186 PGC2018-094572-BI00(MCIU/AEI/FEDER,EU) RNM-199 RNM-325
Keywords: Talco; Vermiculita; Mineralogía; Exsolution; Phengite; Talc; Vermiculite; Transmission-analytical electron microscopy